Harvest Time Can Affect the Optimal Yield and Quality of Sea Lettuce (Ulva fenestrata) in a Sustainable Sea-Based Cultivation - Steinhagen, Sophie; Enge, Swantje; Cervin, Gunnar; Larsson, Karin; Edlund, Ulrica; Schmidt, Alina E. M.; Wahlström, Niklas; Kollander, Barbro; Pavia, Henrik; Undeland, Ingrid; Toth, Gunilla B. (Frontiers in Marine Science, 2022)
Seaweed biomass is a renewable resource with multiple applications. Sea-based cultivation of seaweeds can provide high biomass yields, low construction, operation, and maintenance costs and could offer an environmentally and economically sustainable alternative to land-based cultivations. The biochemical profile of sea-grown biomass depends on seasonal variation in environmental factors, and the optimization of harvest time is important for the quality of the produced biomass. To identify optimal harvest times of Swedish sea-based cultivated sea lettuce (Ulva fenestrata), this study monitored biomass yield, morphology, chemical composition, fertility, and biofouling at five different harvesting times in April - June 2020. The highest biomass yields (approx. 1.2 kg fw [m rope]-1) were observed in late spring (May). The number and size of holes in the thalli and the amount of fertile and fouled tissue increased with prolonged growth season, which together led to a significant decline in both biomass yield and quality during summer (June). Early spring (April) conditions were optimal for obtaining high fatty acid, protein, biochar, phenolic, and pigment contents in the biomass, whereas carbohydrate and ash content, as well as essential and non-essential elements, increased later in the growth season. Our study results show that the optimal harvest time of sea-based cultivated U. fenestrata depends on the downstream application of the biomass and must be carefully selected to balance yield, quality, and desired biochemical contents to maximize the output of future sea-based algal cultivations in the European Northern Hemisphere.